2019
DOI: 10.1155/2019/3546294
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine in the Pathophysiology of Preeclampsia and Gestational Hypertension: Monoamine Oxidase (MAO) and Catechol-O-methyl Transferase (COMT) as Possible Mechanisms

Abstract: Purpose of the Review Hypertension in pregnancy is the global health burden. Amongst the hypertensive disorders of pregnancy, preeclampsia and gestational hypertension are the world's leading disorders that lead to both maternal and fetal morbidity and mortality. Recent Findings Dopamine inactive metabolites, namely, monoamine oxidase (MAO) and catechol-O-methyl transferase (COMT), have been reported to be associated with hypertensive disorders of pregnancy such preeclampsia and gestational hypertension. Summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Another hypertensive disorder of pregnancy that is similar to preeclampsia is gestational hypertension (GH). Gestational hypertension is defined as pregnancy-induced hypertension without proteinuria [ 71 , 72 ]. Both PE and GH oxidative stress are noted as the primary factors that lead to the pathogenesis and pathophysiology of each disease [ 72 ].…”
Section: Oxidative Stress In Gestational Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another hypertensive disorder of pregnancy that is similar to preeclampsia is gestational hypertension (GH). Gestational hypertension is defined as pregnancy-induced hypertension without proteinuria [ 71 , 72 ]. Both PE and GH oxidative stress are noted as the primary factors that lead to the pathogenesis and pathophysiology of each disease [ 72 ].…”
Section: Oxidative Stress In Gestational Hypertensionmentioning
confidence: 99%
“…Gestational hypertension is defined as pregnancy-induced hypertension without proteinuria [ 71 , 72 ]. Both PE and GH oxidative stress are noted as the primary factors that lead to the pathogenesis and pathophysiology of each disease [ 72 ]. A study by Kurlak et al, which investigated oxidative stress profiles in hypertensive states (PE and GH), indicated that oxidative stress profiles do not differ in hypertensive states [ 71 ].…”
Section: Oxidative Stress In Gestational Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that MAO is a major source of deleterious reactive oxygen species (ROS), regulating cardiomyocyte aging or death ( 45 , 46 ). Myocardial ROS are involved in the pathophysiology of cardiovascular diseases such as hypertension and heart failure ( 47 , 48 ), and are important markers of atrial fibrillation in patients after cardiac surgery ( 49 ). Thus, MAO inhibition therapy is protective in several settings of cardiac stresses such as pressure overload heart failure, diabetic cardiomyopathy and chronic ischemic heart disease ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is the main degrading enzyme involved in the degradation of catecholamines in the cerebral cortex, which preferentially affects prefrontal cortical dopamine metabolism. [ 3 , 4 ] The gene encoding COMT is located on chromosome 22q11.2 and contains a functional polymorphism (rs4680). In the gene sequence of codon 158, a nucleotide change from guanine to adenine (G to A), resulting in substituting valine for methionine reduces the COMT enzyme activity three to four-folds.…”
Section: Introductionmentioning
confidence: 99%